ESG Disclosure, Financial Reporting Quality and Investment Efficiency - Choiriah, Siti; Tarmidi, Deden; Ahmad, Zamri (Universitas Pendidikan Ganesha, 2024)
This research discusses the relationship between environmental, social and governance disclosure (ESG Disclosure), financial reporting quality and investment efficiency. This research aims to analyze the influence of ESG disclosure and financial reporting quality on investment efficiency with audit quality as a moderating variable. This research uses quantitative methods with secondary data, companies listed on the BEI ESG Index for 2018 – 2022. These findings also show that the impact of FRQ on investment efficiency decreases with shorter maturities. Research shows good ESG disclosure contributes to investment efficiency by reducing information asymmetry between companies and investors. However, high-quality financial reporting can have a negative impact on investment efficiency because quality financial reports do not necessarily reflect the actual condition of the company. Audit quality factors do not significantly influence the relationship between ESG disclosure, financial reporting quality, or investment efficiency.